Pengaruh Substitusi Tepung Ketan dengan Pati Sagu terhadap Kadar Air, Konsistensi dan Sifat Oragonoleptik Dodol Susu - Dj. Rodisi; I. Suryo; S. Iswanto (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2006)
The objective of this research was to study the effect of substitution of sticky rice flour with sago flour on the quality of milk sweet pastry. As treatments, the sticky rice flour was substituted with 5 levels of sago flour: 0, 25, 50, 75 and 100 %. Each treatment consisted of 3 replicates. Parameter measured included: moisture content, consistency and organolptic characters. Data were statistically analyzed by variance analysis in randomized block design (RBD) and followed with Duncan’s Multiple Range test. The results showed that the use of sago flour in different levels gave highly significant effect (P<0.01) on moisture content, consistency and texture of pastry. Subtitution of sticky rice flour by 50 % of sago flour produced the best quality of pastry.